Adverse Effects of Body-Image Advertising on Women - Bansal, Harbhajan; Dhaka, Ajay (Indian Journal of Marketing, 2006)
She is athletic, but she never sweats. She is beautiful but wears no make up. She is working, but never tired. Aging, but not wrinkled. Breath taking, but brainless. Intelligent but humourless.She is everything. She is nothing. She is advertising to women. -Lazier Smith A tall, slender, coke bottle figured, bikini clad woman appears from the sea-surf. Every body sitting at the beach (of course males) looks at her voyeuristically. She approaches one and says, "Don’t you think, I am hot?" The man in turn wraps his coat around her naked shoulders and says, "It’ll cool you off". Tagline comes-Chillers from Harry collection. Is this the only way to convey the desired message to the target audience? We are inundated with such kind of advertisements throughout the day beginning from early morning to late night. Be it the advertisement for dress material, cell phones, tourism promotion, automobiles or even for cycles the presence of woman model is necessary. In many instances, she is not even needed in the advertisement nor does she has any relation with the product but still she is used as a decorative piece or just to attract attention of the viewer.